2007
DOI: 10.7589/0090-3558-43.3.485
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Visitation and Removal of Baits for Delivery of Pharmaceuticals to Feral Swine

Abstract: ABSTRACT:Within the domestic swine industry there is growing trepidation about the role feral swine (Sus scrofa) play in the maintenance and transmission of important swine diseases. Innovative disease management tools for feral swine are needed. We used field trials conducted in southern Texas from February to March 2006 to compare species-specific visitation and removal rates of fish-flavored and vegetable-flavored baits with and without commercially available raccoon (Procyon lotor) repellent (trial 1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 9 publications
5
38
0
Order By: Relevance
“…An alternative explanation may be that some breeds of cattle find PIGOUT baits to be more palatable than do other breeds (S. J. Lapidge, Invasive Animals Cooperative Research Centre, unpublished data). For example, the Santa Cruz breed was stocked in Campbell and Long (2007) and during our trial 1, whereas the Brahman breed was stocked during our trial 2.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An alternative explanation may be that some breeds of cattle find PIGOUT baits to be more palatable than do other breeds (S. J. Lapidge, Invasive Animals Cooperative Research Centre, unpublished data). For example, the Santa Cruz breed was stocked in Campbell and Long (2007) and during our trial 1, whereas the Brahman breed was stocked during our trial 2.…”
Section: Discussionmentioning
confidence: 99%
“…From an island population in Georgia, Fletcher et al (1990) concluded that oral vaccine delivery to feral swine was feasible and Kavanaugh and Linhart (2000) determined baits could be used to administer pharmaceuticals orally to feral swine. In southern Texas, USA, researchers found high removal (Campbell and Long 2007) and consumption (Campbell et al 2006) of both fish-flavored and vegetable-flavored PIGOUTt feral pig bait (Animal Control Technologies Australia P/L, Somerton, Victoria, Australia). However, removal and consumption was also great for nontarget animals (Campbell et al 2006, Campbell andLong 2007), a discovery inconsistent with findings for PIGOUT baits evaluated in Australia (Cowled et al 2006a, b).…”
Section: Strawberry-flavored Baits For Pharmaceutical Delivery To Fermentioning
confidence: 99%
See 2 more Smart Citations
“…1 Prior investigations of baits intended for pharmaceutical delivery to feral swine in the United States have found that the concept is feasible, 9 but that there are challenges in developing species-specifi c baits for feral swine. 10,11 These studies have led to the creation of relatively inexpensive prototypes of nontarget exclusion feeder systems (NEFS) for feral swine. None of these feeder systems has been evaluated in the United States.…”
mentioning
confidence: 99%